2021
DOI: 10.1177/00187208211050137
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hazard Statement Design Elements in Procedures: Counterintuitive Findings and Implications for Standards

Abstract: Objective The objective of these studies was to identify hazard statement (HS) design elements in procedures that affected whether both workers and lab participants performed the associated hazard mitigation. Background Many of the incidents in high-risk industries are the result of issues with procedures (e.g., standard operating procedures; SOPs) workers use to support their performance. HSs in these procedures are meant to communicate potential work hazards and methods of mitigating those hazards. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(23 citation statements)
references
References 34 publications
1
19
3
Order By: Relevance
“…Do not include critical safety information at the end of a procedure. Although it may be best practice to read the entire procedure before starting a protocol, personnel often do not, so procedure writers should not assume they will. Consistent findings from NGAP’s studies have found that calling out special instructions or hazards using color highlighting or boxes is ineffective for having personnel engage in the desired behavior . Interestingly, this is often counter to guidance from standards .…”
Section: Creating a Standard Operating Proceduresmentioning
confidence: 79%
See 4 more Smart Citations
“…Do not include critical safety information at the end of a procedure. Although it may be best practice to read the entire procedure before starting a protocol, personnel often do not, so procedure writers should not assume they will. Consistent findings from NGAP’s studies have found that calling out special instructions or hazards using color highlighting or boxes is ineffective for having personnel engage in the desired behavior . Interestingly, this is often counter to guidance from standards .…”
Section: Creating a Standard Operating Proceduresmentioning
confidence: 79%
“…Consistent findings from NGAP’s studies have found that calling out special instructions or hazards using color highlighting or boxes is ineffective for having personnel engage in the desired behavior . Interestingly, this is often counter to guidance from standards .…”
Section: Creating a Standard Operating Proceduresmentioning
confidence: 79%
See 3 more Smart Citations